Synthesis and Preclinical Evaluation of Radio-Iodinated GRPR/PSMA Bispecific Heterodimers for the Theranostics Application in Prostate Cancer - Ayman Abouzayed; Cheng-Bin Yim; Bogdan Mitran; Sara S. Rinne; Vladimir Tolmachev; Mats Larhed; Ulrika Rosenström; Anna Orlova (MDPI AG, 2019)
Gastrin-releasing peptide receptor (GRPR) and prostate-specific membrane antigen (PSMA) are overexpressed in most prostate cancers. GRPR expression is higher in early stages while PSMA expression increases with progression. The possibility of targeting both markers with a single theranostics radiotracer could improve patient management. Three GRPR/PSMA-targeting bispecific heterodimers (urea derivative PSMA-617 and bombesin-based antagonist RM26 linked via X-triazolyl-Tyr-PEG2, X = PEG2 (BO530), (CH2)8 (BO535), none (BO536)) were synthesized by solid-phase peptide synthesis. Peptides were radio-iodinated and evaluated in vitro for binding specificity, cellular retention, and affinity. In vivo specificity for all heterodimers was studied in PC-3 (GRPR-positive) and LNCaP (PSMA-positive) xenografts. [125I]I-BO530 was evaluated in PC-3pip (GRPR/PSMA-positive) xenografts. Micro single-photon emission computed tomography/computed tomography (microSPECT/CT) scans were acquired. The heterodimers were radiolabeled with high radiochemical yields, bound specifically to both targets, and demonstrated high degree of activity retention in PC-3pip cells. Only [125I]I-BO530 demonstrated in vivo specificity to both targets. A biodistribution study of [125I]I-BO530 in PC-3pip xenografted mice showed high tumor activity uptake (30%−35%ID/g at 3 h post injection (pi)). Activity uptake in tumors was stable and exceeded all other organs 24 h pi. Activity uptake decreased only two-fold 72 h pi. The GRPR/PSMA-targeting heterodimer [125I]I-BO530 is a promising agent for theranostics application in prostate cancer.